Moving beyond feedback: Energy behaviour and local engagement in the United Kingdom. (July 2015) - Bull, Richard; Lemon, Mark; Everitt, Dave; Stuart, Graeme
Highlights: Social media and smartphones offer potential to move beyond feedback. Building users recognise the energy savings potential around greater engagement. Unless responsibilities are woven into everyday roles, and not separated out into an 'energy department' this problem will remain. Abstract: The energy savings potential within non-domestic buildings from behaviour change initiatives is well known. Energy efficiency measures can contribute to local, national and EU policy commitments on carbon reduction. Yet, research also shows behaviour change is anything but simple. No-where is this more evident that in local government where municipalities are expected to lead on carbon reduction initiatives whilst operating in challenging political landscapes. This paper reflects on a UK Research Council funded case study exploring the role of engagement in a UK municipality. Innovative feedback tools and user-engagement were developed in an effort to foster a collaborative approach to energy management. Findings from an analysis of a focus group and a set of semi-structured interviews show encouraging signs with regard to increased user-engagement and digital tools, but barriers remain with regards to the 'real world' implementation of innovative, and technologically grounded, approaches. These included a staff reduction programme amidst financial cuts, a risk-averse culture with regard to new technologies, and debate about where responsibilities lie with regards to energy management. While these findings were case specific they have implications for organisations contemplating how technology might support them in workplace engagement for reduced energy use.